Effect of diamagnetic contribution of water on harmonics distribution in a dilute solution of iron oxide nanoparticles measured using high-Tc SQUID magnetometer - Mohd Mawardi, Saari; Tsukamoto, Yuya; Kusaka, Toki; Ishihara, Yuichi; Sakai, Kenji; Kiwa, Toshihiko; Tsukada, Keiji (Elsevier Ltd, 2015)
The magnetization curve of iron oxide nanoparticles in low-concentration solutions was investigated by a highly sensitive high-Tc superconducting quantum interference device (SQUID) magnetometer. The diamagnetic contribution of water that was used as the carrier liquid was observed in the measured magnetization curves in the high magnetic field region over 100 mT. The effect of the diamagnetic contribution of water on the generation of harmonics during the application of AC and DC magnetic fields was simulated on the basis of measured magnetization curves. Although the diamagnetic effect depends on concentration, a linear relation was observed between the detected harmonics and concentration in the simulated and measured results. The simulation results suggested that improvement could be expected in harmonics generation because of the diamagnetic effect when the iron concentration was lower than 72 μg/ml. The use of second harmonics with an appropriate bias of the DC magnetic field could be utilized for realization of a fast and highly sensitive detection of magnetic nanoparticles in a low-concentration solution.